HLA-G 14bp Ins/Del Polymorphism, Plasma Level of Soluble HLA-G, and Association with IL-6/IL-10 Ratio and Survival of Glioma Patients - Bucova, Maria; Kluckova, Kristina; Kozak, Jan; Rychly, Boris; Suchankova, Magda; Svajdler, Marian; Matejcik, Viktor; Steno, Juraj; Zsemlye, Eszter; Durmanova, Vladimira (Diagnostics, 2022)
HLA-G is an immune checkpoint molecule with immunosuppressive and anti-inflammatory activities, and its expression and level of its soluble form (sHLA-G) may play an important role in tumor prognosis. The HLA-G 14bp ins/del polymorphism and the plasma level of soluble HLA-G (sHLA-G) were investigated by a polymerase chain reaction and ELISA, respectively, in 59 glioma patients. A significantly higher proportion of glioma patients had the 14 nt insert in both homozygous and heterozygous states compared to the control group. Glioma patients also had higher plasma levels of sHLA-G. Patients with methylated MGMT promoters had lower levels of sHLA-G than those with unmethylated MGMT promoters. The level of sHLA-G negatively correlated with the overall survival of patients. Glioblastoma patients who survived more than one year after diagnosis had lower levels of sHLA-G than those surviving less than one year. Patients with sHLA-G levels below the cut-off value of 40 U/mL survived significantly longer than patients with sHLA-G levels above 40 U/mL. The levels of sHLA-G were also negatively correlated with the level of IL-6 (p = 0.0004) and positively with IL-10/IL-6 (p = 0.046). Conclusion: The presence of the 14 nt insert in both homozygous and heterozygous states of the HLA-G 14bp ins/del polymorphism is more frequent in glioma patients and the elevated plasma levels of sHLA-G are negatively associated with their survival.